Morphological and molecular characterization of Maritrema kostadinovae n. sp. (Digenea: Microphallidae) from the yellow-crowned night heron Nyctanassa violacea (Aves: Ardeidae) in Mexico - Hernández-Orts, Jesús S; Capasso, Sofía; Pinacho-Pinacho, Carlos D; García-Varela, Martín (Parasitology research, 2020)
A new species of microphallid trematode was collected from the intestine of the yellow-crowned night heron Nyctanassa violacea (L.) (Pelecaniformes: Ardeidae) from Veracruz, Mexico. Maritrema kostadinovae n. sp. differs distinctly from other members of Maritrema Nicoll, 1907 from the Americas by its smaller body size (262-435 × 242-363 μm), the extension of caeca (reaching to anterior level of ventral sucker), the size and shape of the cirrus (short, tubular and unarmed) and metraterm (simple and thin-walled), the position of the genital pore (sinistrolateral to ventral sucker) and the arrangement of the vitellaria (horseshoe-shaped with posteriorly directed opening). Maximum likelihood and Bayesian inference analyses, based on partial 28S rDNA sequences, depicted M. kostadinovae n. sp. within the genus Maritrema with strong support. The new species is in a sister position to other available members of Maritrema, except for M. subdolum Jägerskiöld, 1909 that branches as the early divergent species in the Maritrema clade. The new species is the third species of Maritrema described from birds in Mexico. Comparative morphometric data for Maritrema taxa from birds and mammals from the Americas is provided.
Keywords: Taxonomy; Wading birds; Mexiko; 28S rDNA; Mexico; DNA, Helminth; Trematode Infections; Birds; DNA, Ribosomal; North America; zvířata; DNA helmintů; fylogeneze; ribozomální DNA; Species Specificity; Trematoda; druhová specificita; ptáci; Phylogeny; infekce červy třídy Trematoda; Animals